Simple Decision Making In Renewable Energy Planning - Saputra, Rahmad Surya Hadi; A, Sulaiman; Tahir, Usman; Judijanto, Loso (Pt. Anagata Sembagi Education, 2025)
Renewable energy planning is a complex process, involving multiple dimensions, including natural resource availability, government policies, and socio-economic factors. This study emphasizes the importance of a decision-making approach that is not only technically based, but also considers the social and political factors that influence policy implementation. Decision-making in renewable energy planning is often hampered by information inequality between stakeholders, social resistance, and policy instability that can slow down a sustainable energy transition. Multi-Criteria Decision Making (MCDM) methods have been used to help stakeholders choose the best option, but overly technical approaches can be a barrier in developing countries. Therefore, simpler and more data-driven approaches, such as heuristic models, become more relevant in contexts of uncertainty. This research uses a descriptive qualitative approach through case studies to explore the dynamics of decision-making in renewable energy planning. Data were collected through in-depth interviews, focus group discussions (FGDs), and document analysis. The results show that transparency, open communication and stakeholder participation are essential to overcome social and political barriers and support effective and sustainable renewable energy policy implementation.